CYP1A2 Genetic Polymorphism Is Associated With Treatment Remission to Antidepressant Venlafaxine in Han Chinese Population. Issue 2 (March 2019) - Zhu, Yuhao; Zhang, Naixing; Ren, Decheng; Bi, Yan; Xu, Fei; Niu, Weibo; Sun, Qianqian; Guo, Zhenming; Yuan, Ruixue; Yuan, Fan; Wu, Xi; Cao, Yanfei; et al.
Abstract : Abstract: Major depressive disorder (MDD) is a common mental disorder. Venlafaxine (VEN) is used to treat patients with MDD as an antidepressant of serotonin-norepinephrine reuptake inhibitor. In addition, current reports reveal that CYP enzymes mediate its metabolism, thereby affecting the treatment efficacy. The aim of this study was to test whether the genetic polymorphisms of CYP1A2 are associated with remission after VEN treatment for MDD. A total of 175 Han Chinese depressed patients have been recruited to accept a 6-week treatment with VEN. Three single-nucleotide polymorphisms of CYP1A2 were selected from dbSNP and previous literature to compare the allele and genotype frequencies between remitters and nonremitters. The A 17-item Hamilton Depression Scale was used to access the improvement of patients' depressive symptoms from the baseline to endpoint. A logistic regression analysis for remission was conducted. Between remitters and nonremitters, the allele and genotype frequencies of single-nucleotide polymorphism rs2470890 demonstrated significant differences. They still had significant differences between remitters and nonremitters after controlling baseline Hamilton Depression Scale scores, sex, and age in logistic regression. Our results suggest that the single-nucleotide polymorphism rs2470890 of CYP1A2 gene might be associated with treatment remission after VEN treatment in patients with MDD.